Teaching Vocabulary by Using Semantic Mapping Strategy (Quasy Experimental Study on the Seventh Graders Students of SMP Mandiri Pontianak Timur In Academic Years 2017/2018) - Zulkarnaen (LPPM STBA Pontianak, 2017)
This research was conducted to answer the research question: “How effective is the use of Semantic Mapping to increase vocabularyachievement on the Seventh Graders Students of SMP Mandiri Pontianak?” method of this research is a Quasi-experimental Study. A Quasi-experimental Study requires one experimental group and one control group and needs the test namely Pretest and Posttest. The treatments were conducted in three time meetings with the purpose of knowing the effectiveness of the teaching of vocabulary using Semantic Mapping. The research findings showed the mean score of pretest in experimental group is 6,70 and the mean score of posttest is 7,82 and categorized “.good”. The result of computation on the t-test with 2,70 is higher than the t-table for the degree of freedom N-1 (60-1)=59 is 2,021. Moreover, the computation on Effect Size of the treatment is 2,01. It is categorized “highly effective” because the result of 2,02 is higher than 0.8 that is the high level of effectiveness on Effect Size criteia proposed by Burn (ES > 0.8 = 2,01 >0.8). From the computation, it can be concluded that the teaching of vocabulary by using Semantic Mapping “highly effective”. Therefore, the null hypothesis that says “The use of Semantic Mapping is not effective to increase the students’ vocabulary achievement” is rejected. And the alternative hypothesis that says “The use of Semantic Mapping is effective to increase the students’ vocabulary achievement is effective” is accepted.